2011
DOI: 10.1094/pdis-12-10-0922
|View full text |Cite
|
Sign up to set email alerts
|

First Report of the β-Tubulin E198A Mutation Conferring Resistance to Methyl Benzimidazole Carbamates in European Isolates of Monilinia fructicola

Abstract: The causal agent of brown rot on stone and pome fruits, Monilinia fructicola (G. Wint.), is a quarantine pathogen in Europe. It has been detected in Austria (later eradicated), Spain, the Czech Republic, Italy, Germany, and Switzerland (1). In the United States and other countries, M. fructicola isolates were reported to show resistance to different classes of fungicides, including methyl benzimidazole carbamates (MBC) (2). Lichou et al. (2) reported the presence of isolates resistant to the MBC carbendazim in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In a recent study that included four M. fructicola isolates of our population, it was demonstrated that mutations leading to high levels of resistance to MBC fungicides were present in Europe (Weger et al 2011). Despite the fact that resistance to fungicides has been also detected in M. laxa populations in Europe (Thomidis et al 2009;Malandrakis et al 2012Malandrakis et al , 2013, we have no detected resistance to MBCs, DFCs or DMIs until 2006, in our M. laxa study population.…”
Section: Introductionmentioning
confidence: 59%
“…In a recent study that included four M. fructicola isolates of our population, it was demonstrated that mutations leading to high levels of resistance to MBC fungicides were present in Europe (Weger et al 2011). Despite the fact that resistance to fungicides has been also detected in M. laxa populations in Europe (Thomidis et al 2009;Malandrakis et al 2012Malandrakis et al , 2013, we have no detected resistance to MBCs, DFCs or DMIs until 2006, in our M. laxa study population.…”
Section: Introductionmentioning
confidence: 59%
“…Furthermore, rare alleles from the source population may become common in the new population if they are present in the founders of this new population (Milgroom et al 1992). Weger et al (2011) has proposed that these processes could explain the high levels of resistance against methyl benzimidazole carbamate (MBC) that has been found in some M. fructicola isolates from Italy, France, Spain, and Switzerland posing a significant risk for peach production in the Ebro Valley, Spain, where M. fructicola is now present. Disease management programs against M. fructicola should take this into account in order to slow down the development of fungicidal-resistant strains.…”
Section: Discussionmentioning
confidence: 99%
“…However, fungicide-based methods are not sustainable in the long term because of the emergence and subsequent spread of M. fructicola and M. laxa strains with reduced sensitivity to fungicides (Egüen et al, 2015;Ma et al, 2005;Malandrakis et al, 2013;Thomidis et al, 2009;Weger et al, 2011;. Recent studies in the Ebro Valley have detected a M. fructicola population with isolates that were single resistant, double resistant, or even triple resistant to tiophanate-methyl, iprodione and tebuconazole (Egüen et al, 2015).…”
Section: Intrinsic Host Resistancementioning
confidence: 99%
“…11). Furthermore, since 2014 M. (Weger et al, 2011). Due to the extended usage of molecular tools in disease diagnostic, it has been discovered that there are at least six species causing brown rot on Prunus spp., three more species than the initialy described (M. fructicola, M. fructigena, and M. laxa).…”
Section: Introduction 21mentioning
confidence: 99%